Ethnofolism and facets of ethnic tolerance - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article examines the problem of the axiological connotation of secondary ethnonyms. It is argued that ethnopholisms are not only a linguistic phenomenon, but also a sociocultural one, and their study requires a philosophical approach. The article emphasises that in the context of intense migration processes and global instability, it is crucial to identify and prevent the escalation of ethnocultural tensions or potential conflicts. The article explores the essence of ethnopholisms, highlighting their diversity and functional characteristics. The concepts of exoethnonym and endoethnonym (autoethnonym) are distinguished, and the correlation between the self-designation of an ethnic community and auto- and heterostereotypes are emphasised. It is proven that the use of ethnopholisms is a peculiar indicator of interethnic tension.